MODERN RISK ANALYSIS IN THE PLANNING AND IMPLEMENTATION OF MODERNIZATION PROJECTS IN RAILWAY INFRASTRUCTURE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The implementation of modernization projects in railway infrastructure is accompanied by a number of risks that affect their successful implementation within the planned budget and time. In general, risks are considered as technical, financial, environmental and social. The identification and management of these risks is essential for the successful implementation of the project within the set scope, and this has an impact on the provision of modern and safe rail transport. Modern approaches to detailed planning and risk assessment, as well as the implementation of new monitoring technologies contribute to successful transport projects. The modern approach to risk management devotes a special role to public participation. The goal is to minimize social tension and achieve a better understanding of projects on the part of the population. This study analyzes and improves risk management methods for planning and implementing railway infrastructure modernization projects.